Masculinity might be more toxic than we think: The influence of gender roles on trait emotional manipulation. (1st February 2019) - Grieve, Rachel; March, Evita; Van Doorn, George
Abstract: Previous research has established sex differences in emotional manipulation; specifically, men are more likely than women to engage in emotional manipulation. This study aimed to explicate these sex differences by investigating, for the first time, the influence of gender roles in the prediction of trait emotional manipulation. Participants were 435 females and 139 males ( N  = 574) who reported their levels of masculine and feminine gender roles, as well as primary and secondary psychopathy, trait emotional intelligence, and trait emotional manipulation. Separate regressions were conducted for each sex. As predicted, for both males and females, masculine gender roles positively predicted emotional manipulation. For males, no other predictors were significant, however there was evidence of statistical suppression for feminine gender roles. For females, low female gender roles, high primary and secondary psychopathy, and high emotional intelligence all significantly predicted emotional manipulation; the effect of emotional intelligence was via statistical suppression. This study represents an important first step in understanding the interplay between socialisation and emotional manipulation. Future research would benefit from using a longitudinal approach to determine whether emotional manipulation can be reduced through shifting gender roles. Highlights: First study examining sex differences in emotional manipulation using gender roles. For males, ↑masculine gender roles were associated with ↑emotional manipulation (EM). For females, ↑masculine gender roles were associated with ↑EM. For females, ↓feminine gender roles were associated with ↑EM. Primary and secondary psychopathy and emotional intelligence predicted EM in females.